2015
DOI: 10.11648/j.ijcda.20150103.14
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Supply of Sciatic Nerve and Its Impact on Clinical Practice

Abstract: Sciatic nerve is the nerve of the posterior compartment of thigh; it is formed in the pelvis from the ventral rami of L4 to S3 spinal nerves. It leaves the pelvis via the greater sciatic foramen below piriformis and divides into common peroneal nerve and tibial nerve at the level of the upper angle of the popliteal fossa. The vasculature of peripheral nerves is adapted specifically to their structure and function. Arterial vessels that reach main nerve trunks originate from the adjacent main arteries or their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The ascending branch supplies the anterolateral part of the gluteal region and the greater trochanter of the femur, the transverse branch wraps around the neck of the femur and contributes to the cruciate anastomosis, and the descending branch runs deep to the rectus femoris and medial to vastus lateralis all the way up to the knee joint to join the genicular anastomosis [3]. A study reported that the LCFA also contributes to the vascular supply of the sciatic nerve in up to 25% of dissected cadavers [4].…”
Section: Introductionmentioning
confidence: 99%
“…The ascending branch supplies the anterolateral part of the gluteal region and the greater trochanter of the femur, the transverse branch wraps around the neck of the femur and contributes to the cruciate anastomosis, and the descending branch runs deep to the rectus femoris and medial to vastus lateralis all the way up to the knee joint to join the genicular anastomosis [3]. A study reported that the LCFA also contributes to the vascular supply of the sciatic nerve in up to 25% of dissected cadavers [4].…”
Section: Introductionmentioning
confidence: 99%